(untitled) (International relations and international law Journal, 2020)
The main goal of the article is to reassess and analyze difficulties and obstacles in the way of business relations between the Republic of Kazakhstan and the People’s Republic of China in the context of the international economic crisis. Kazakhstan and China are historically and geographically neighbors, and it is clear that we will enter into political, cultural, economic and military relations with a neighboring country, whether we want it or not. At present, Kazakhstan has such views as anti-Chinese sentiment, the “Chinese threat”, and there are reasons for that. If we take into account our eternal neighborhood and close trade and economic relations, we should consider China, a country with huge economic potential, not only in terms of threats and fears, but also as a new opportunity for Kazakhstan, while maintaining the integrity and sovereignty of the country. Since gaining independence, Kazakhstan has established friendly and partnership relations with the People’s Republic of China, having completely resolved the issue of the border between the two countries, and today has established relations as a new strategic partner. However, there are key problems between the two countries. We see that there are many political, legal, regulatory, cultural and ideological barriers to the development of business relations. This article can help us to understand some of them. Key words: Republic of Kazakhstan, People’s Republic of China, business relations, foreign policy.